Within and Among - Brad Cloepfil (Oz, 2015)
The existing forces embodied by a site are what we commonly refer to as context. An awareness of context implies a relative positioning of the self. I am here, among these buildings, or within this field, at this place in the history of ideas and technology. In acknowledging surroundings as specific, as forged or affected by particular physical or cultural forces, experiences or qualities, you have begun a conversation of context.